2011
DOI: 10.1111/j.1399-3038.2011.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Chickenpox in childhood is associated with decreased atopic disorders, IgE, allergic sensitization, and leukocyte subsets

Abstract: WTVZV up to 8 yr of age protects against atopic disorders, which is likely mediated by suppression of IgE production and allergic sensitization, as well as altered leukocyte distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Unconditional logistic regression models were used to calculate odds ratios and 95% confidence intervals (CI) for the associations between glioma status and regular oral antihistamine use, adjusting for potential confounders (which were chosen a priori ). History of chickenpox was included in our models as a potential confounder because a growing body of literature indicates that varicella-zoster exposure may be relevant to glioma risk [3235] and may also potentially impact the risk for atopic conditions [36, 37]. The regression models were run both among the overall study population and stratified by self-reported allergy/asthma status, as antihistamines are sometimes taken regularly for indications other than allergic conditions (i.e., as sleep aids or antiemetics).…”
Section: Methodsmentioning
confidence: 99%
“…Unconditional logistic regression models were used to calculate odds ratios and 95% confidence intervals (CI) for the associations between glioma status and regular oral antihistamine use, adjusting for potential confounders (which were chosen a priori ). History of chickenpox was included in our models as a potential confounder because a growing body of literature indicates that varicella-zoster exposure may be relevant to glioma risk [3235] and may also potentially impact the risk for atopic conditions [36, 37]. The regression models were run both among the overall study population and stratified by self-reported allergy/asthma status, as antihistamines are sometimes taken regularly for indications other than allergic conditions (i.e., as sleep aids or antiemetics).…”
Section: Methodsmentioning
confidence: 99%
“…Several different pathogens have been suggested to have a protective role against AD and atopy in general, including bacterial endotoxins, helminthes, herpesviridae, farm animals, dogs, unpasteurized milk, and the abundant infectious exposures of early day care [70][71][72][73][74]. Silverberg et al found that a single episode of wild-type varicellazoster virus (chickenpox) infection in the first 8-10 years of life was inversely associated with subsequently developing AD [73], as well as long-term decreased serum IgE levels, peripheral blood lymphocyte, monocyte, and basophil counts [75].…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…While herpesvirus infections early in life may help prevent AD, infections with herpes simplex and Coxsackie virus in patients with established AD can lead to eczema herpeticum and Coxsakium, respectively [136,137]. Moreover, some studies found that infections with respiratory syncytial virus may actually increase the risk of disease [73,[75][76][77][78]. Finally, it is well established that patients with AD have increased colonization of both lesional and nonlesional skin with Staphylococcal aureus and decreased microbial diversity [79][80][81][82].…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…We previously reported that exposure to varicella zoster virus in early childhood was associated with lower odds of developing AD, 10 asthma, and hay fever, as well as decreased serum IgE, allergic sensitization, and persistent alterations of leukocyte subsets. 11 It would be expected that immigrants to the United States from developing countries, where infectious stimuli are more prevalent, would have a lower risk of allergic disease.…”
mentioning
confidence: 99%